Microwave Accelerated 1,3-Dipolar Cycloaddition Reactions of Cyclopentylidene N-Phenyl Nitrone with Substituted N-Arylmaleimides - SINGH, MANJIT; SINGH, BALDEV; KRISHAN SINGAL, KEWAL (Asian Journal of Chemistry, 2010)
Microwave accelerated 1,3-dipolar cycloaddition reactions of cyclopentylidene N-phenyl nitrone with substituted N-arylmaleimides leading to synthesis of new 2,5-diaryl-3, 3-spirotetramethylene-4H- 2,3,3a, 5,6,6a-hexahydropyrrolo[3,4-d] isoxazole-4, 6-dione derivatives.